FIRST RECORD OF Dianema urostriatum (MIRANDA RIBEIRO, 1912) (SILURIFORMES: CALLYCHTHIDAE), IN THE PUTUMAYO RIVER, AMAZON BASIN, PERU - Ruiz-Tafur, Morgan; Sánchez Riveiro, Homero; García-Ayala, James [UNESP] (Instituto de Investigaciones de la Amazonia Peruana - IIAP, 2022)
The presence of Dianema urostriatum (Miranda Ribeiro, 1912), is formally reported in tributaries of the Putumayo River, Perú, expanding its geographic distribution of the Amazon basin. This record enriches the Peruvian continental ichthyofauna.
PRIMER REGISTRO DE Dianema urostriatum (MIRANDA RIBEIRO, 1912) (SILURIFORMES: CALLYCHTHIDAE), EN EL RÍO PUTUMAYO, CUENCA DEL AMAZONAS, PERÚ
Keywords: Conservation; freshwater fish; Neotropical region